Effects of Polyethersulfone Membrane Substrate on the Separation Performance of Thin Film Composite Membrane in Biorefinery - Siti Normunira, Ramli; Syed Mohd Saufi, Tuan Chik; Mazrul Nizam, Abu Seman; Hafizuddin, Wan Yussof; Abdul Wahab, Mohammad (AIDIC Servizi, 2017)
This study was aimed to develop a customised thin film composite (TFC) membrane for the separation in biorefinery. After the biomass hydrolysis stage, sugars component (i.e. glucose and xylose) need further refinement to remove any inhibitor (i.e. acetic acid) that can decrease the yield of the product during the fermentation stage. Substrate layer properties and the condition of thin film formation during interfacial polymerisation (IP) influenced the performance of the TFC membrane. Not much attention is given on the effects of substrate membrane properties asmost support membranes were purchased commercially. Polyethersulfone (PES) membrane substrate was fabricated in the current study at different PES concentration range of 15 wt% to 23 wt%. IP was performed using the piperazine and trimesoyl chloride monomers. As the PES concentration in the membrane substrate increased, the pure water permeability (PWP) decreased. The PWP of the membrane substrate prepared from 15 % PES and 23 % PES were 231.67 ± 16.59 L/m2.h.bar and 24.49 ± 6.54 L/m2.h.bar. After the IP, the PWP decreased to the range of nanofiltration. The PWP value were 28.07 ± 5.42 L/m2.h.bar and 3.94 ± 1.21 L/m2.h.bar for the TFC membrane prepared using 15 % PES and 23 % PES membrane support. TFC membrane prepared using 23 % PES showed the rejection value 24.07 ± 5.96 % of xylose, 47.56 ± 1.99 % of glucose and 2.67 ± 1.05 % of acetic acid. This is corresponding to the ideal separation factor of 1.45 ± 0.06 for xylose/glucose, 1.86 ± 0.05 for acetic acid/glucose and 1.29 ± 0.09 for acetic acid/xylose.